Innovating Online Birth Certificate Services at the Population and Civil Registry Office of Bula City East Seram Regency - Safarni, Safarni; Soselisa, Pieter Sammy; Rahanra, Ivonny Yeany (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
This study investigates the innovation of online birth certificate services implemented by the Population and Civil Registry Office of Bula City in East Seram Regency. Aimed at simplifying the registration process, the online system allows citizens to apply for and upload the necessary documents without physically visiting the office. Despite its accessibility, the community's understanding and utilization of the system remain limited. The research employed a descriptive qualitative approach, involving 12 informants, to assess the procedures and benefits of this service. Findings reveal that while the online system offers significant time and location flexibility, many residents are still unfamiliar with the online registration process. The research highlights the importance of enhancing public understanding and ensuring that the system is user-friendly. To address this gap, it is recommended that further outreach and education campaigns be implemented to foster greater engagement with the system, alongside continuous improvement of the online service interface.